Analisis terhadap manuskrip al-Quran Terengganu IAMM 2012.13.6 / Riswadi Azmi - Riswadi , Azmi (2018)
The Terengganu al-Quran manuscripts are among the many Quranic manuscripts existing in the Malay world. The accuracy and quality of their illustrations make them among the most beautiful manuscripts of the 18th and 19th centuries. The Terengganu Quran Manuscript IAMM2012.13.6 was chosen for this study as it is the only one of the Terengganu al-Qurans with a complete qiraat record. The main focus of the study is on the history of the Terengganu al-Quran manuscript and its distribution locally and overseas as well as to provide a detailed description of the Terengganu Quran Manuscript IAMM2012.13.6. This study analyzed the textual aspects to determine the techniques and methods used by the writer. For this purpose, the philological approach was used to collect data in addition to using library and historical review sources. Next the text was analyzed using inductive and comparative methods. The findings reveal that the Terengganu al-Quran manuscript was actively produced from the 18th century AD and received the full support of the Terengganu sultanate. An analysis of the texts revealed some minor errors of writing but as a whole it followed closely to the rasm ‘uthmānī method. In regard to ḍabṭ, the focus of the writing is only on the basic signs of reading and includes the waqaf and ibtidā’ aspects, while in terms of fawāṣil there were some errors that resulted in a difference in the number of sentences. The calligraphy used is of the naskhī type while on the qiraat the writer discussed the recitation of seven imams based on the ṭāriq Shāṭibiyyah. This study can contribute to a better understanding of the significance of the Terengganu al-Quran manuscripts and how the efforts involved in producing are evidence of the local wisdom prevailing then which need to be recognized and preserved.